Productivity and nutritional aspects in Moringa oleifera plants fertilized with NPK in south-eastern Brazil - FONTAN, IVAN DA COSTA ILHÉU; SILVA, ENILSON DE BARROS; LAFETÁ, BRUNO OLIVEIRA; SILVA, WEMERSON MARCELO GONÇALVES; NASCIMENTO, SANDRA ANTUNES DO; UANE, BENTO GIL (The Indian Journal of Agricultural Sciences, 2024)
Moringa oleifera is an Asian tree species cultivated for its nutritional and medicinal properties. Present study was carried out during 2021 and 2022 at Federal Institute of Minas Gerais, São João Evangelista-MG, Doce River Valley, South-Eastern Brazil to determine NPK doses for Moringa and critical NPK levels in the shoot. The experimental design was a fractional factorial of the type (1/2)43, with 32 treatments set up in four blocks. The treatments represented combinations of doses of N (0, 40, 80, 160 kg/ha); P2O5 (0, 45, 90, 180 kg/ha); and K2O (0, 20, 40, 80 kg/ha). Each experimental unit was composed of four seedlings arranged in a row. Plant shoot harvests were carried out every 60 days (January, March, May, July, September and November) for two consecutive years. The data were analyzed using regression analysis, and the adjusted response surface model was: Y = b0 + b1 N + b2 N2 + b3 P + b4 P2 + b5 K + b6 K2 + b7 NP + b8 NK + b9 PK. The productivity of fresh and dry matter of the shoot of M. oleifera plants was influenced only by N doses in the first year of cultivation, when the supply of 88.7 and 85.8 kg/ha of N led to the maximum estimated productivity for fresh (10,360.3 kg/ha) and dry matter (2,84.0 kg/ha). The critical contents in the shoot were 3.23 dag/kg (N), 0.41 dag/kg (P), and 2.18 dag/kg (K), while the annual extraction by plants was 78.44 kg/ ha (N), 8.99 kg/ha (P), and 48.81 kg/ha (K).